The The influence of digital content marketing on E-WOM with social impact transfer as mediation for Rendang business owners in Padang City - Mutiara Zorena Rezky; Vidyarini Dwita (Marketing Management Studies, 2022)
This study aims to analyze how the influence of Digital Content Marketing with its dimensions include information content, entertainment content, social interaction and own experience on electronic word of mouth communication in rendang culinary food business actors with the social impact of transfer as a mediating variable (the object of the study on Instagram rendang Asese). The method used is quantitative. The population is all customers who follow Rendang Asese's Instagram account and customers who have recommended others to visit Rendang Asese shopping. The research sample was 150 respondents. This research was conducted using the smart PLS 3.0 software using the structural equation model (SEM) test. The results of this study include: (1) Information content has a significant effect on Social Impact Transfer (2) Entertainment Content has a significant effect on Social Impact Transfer (3) Social interaction has a significant effect on Social Impact Transfer (4) Self-experience has a significant effect on Social Impact Transfer (5) Social Impact Transfer has a significant effect on electronic word of mouth communication (6) Information content has a significant effect on electronic word of mouth communication with Social Impact Transfer as a mediating variable (7) Entertainment Content has a significant effect on electronic word of mouth communication with Social Impact Transfer as a mediating variable ( 8) Social interaction has a significant effect on electronic word of mouth communication with Social Impact Transfer as a mediating variable (9) Self-experience has a significant effect on electronic word of mouth communication with Social Impact Transfer as a mediating variable